2022
DOI: 10.3390/v14071542
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Checkerboard Method for Phage-Antibiotic Synergy Detection

Abstract: Phage-antibiotic synergy is a promising therapeutic strategy, but there is no reliable method for synergism estimation. Although the time-kill curve assay is a gold standard, the method is not appropriate for fast and extensive screening of the synergy. The aim is to optimize the checkerboard method to determine phage-chemical agent interactions, to check its applicability by the time-kill curve method, and to examine whether the synergy can be obtained with both simultaneous and successive applications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
2
Order By: Relevance
“…Recently published studies reported additive or synergistic effects of ciprofloxacin and phage combination (134,(218)(219)(220)(221)(222)(223). Gurney et al reported that phages could interact with different structures of P. aeruginosa, such as lipopolysaccharide structure (LPS) and the efflux pumps.…”
Section: Synergism Of Ciprofloxacin With Bacteriophagesmentioning
confidence: 99%
“…Recently published studies reported additive or synergistic effects of ciprofloxacin and phage combination (134,(218)(219)(220)(221)(222)(223). Gurney et al reported that phages could interact with different structures of P. aeruginosa, such as lipopolysaccharide structure (LPS) and the efflux pumps.…”
Section: Synergism Of Ciprofloxacin With Bacteriophagesmentioning
confidence: 99%
“…These combinations allow the application of antibiotics in sub-inhibitory doses, leading to a reduction in the harmful effects of antibiotics in animals and humans. In addition, the combination of phages with antibiotics can potentiate antibiotic function, prolonging or restoring their activity against bacteria [105,106]. To the authors' best knowledge, this synergism is not fully characterized regarding the application of phages in poultry production; however, it is a factor that should be considered in the development of protocols for the treatment of bacterial infections using bacteriophages.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…The phage lytic efficacy was determined as described by Nikolic et al [22] with few modifications. Briefly, 10-fold dilutions of phage lysates were prepared in 96-well microtiter plates in Mueller-Hinton broth.…”
Section: Phage Lytic Efficacymentioning
confidence: 99%
“…The phage lytic efficacy of bacteriophages was determined by the method described by Nikolic et al [22]. The MOI that prevented bacterial growth was recorded and assigned 'minimal inhibitory MOI' (MIM).…”
Section: Phage Lytic Efficacymentioning
confidence: 99%